Interplay between chromosomal architecture and termination of DNA replication in bacteria - Goodall, Daniel J.; Warecka, Dominika; Hawkins, Michelle; Rudolph, Christian J. (Frontiers in Microbiology, 2023)
Faithful transmission of the genome from one generation to the next is key to life in all cellular organisms. In the majority of bacteria, the genome is comprised of a single circular chromosome that is normally replicated from a single origin, though additional genetic information may be encoded within much smaller extrachromosomal elements called plasmids. By contrast, the genome of a eukaryote is distributed across multiple linear chromosomes, each of which is replicated from multiple origins. The genomes of archaeal species are circular, but are predominantly replicated from multiple origins. In all three cases, replication is bidirectional and terminates when converging replication fork complexes merge and ‘fuse’ as replication of the chromosomal DNA is completed. While the mechanics of replication initiation are quite well understood, exactly what happens during termination is far from clear, although studies in bacterial and eukaryotic models over recent years have started to provide some insight. Bacterial models with a circular chromosome and a single bidirectional origin offer the distinct advantage that there is normally just one fusion event between two replication fork complexes as synthesis terminates. Moreover, whereas termination of replication appears to happen in many bacteria wherever forks happen to meet, termination in some bacterial species, including the well-studied bacteria Escherichia coli and Bacillus subtilis, is more restrictive and confined to a ‘replication fork trap’ region, making termination even more tractable. This region is defined by multiple genomic terminator (ter) sites, which, if bound by specific terminator proteins, form unidirectional fork barriers. In this review we discuss a range of experimental results highlighting how the fork fusion process can trigger significant pathologies that interfere with the successful conclusion of DNA replication, how these pathologies might be resolved in bacteria without a fork trap system and how the acquisition of a fork trap might have provided an alternative and cleaner solution, thus explaining why in bacterial species that have acquired a fork trap system, this system is remarkably well maintained. Finally, we consider how eukaryotic cells can cope with a much-increased number of termination events.